2015
DOI: 10.1016/j.autcon.2014.10.014
|View full text |Cite
|
Sign up to set email alerts
|

Practices and effectiveness of building information modelling in construction projects in China

Abstract: Based on an investigation of 106 projects involving the use of building information modelling (BIM), this paper examines current BIM practices in China, and assesses how various practices alter their effectiveness. The results reveal that in current practice BIM is principally employed as a visualization tool, and how it is implemented is significantly associated with project characteristics. BIM use in the majority of the surveyed projects is seen to have positive outcomes, with the benefits of improved task … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
132
1
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 204 publications
(151 citation statements)
references
References 56 publications
2
132
1
3
Order By: Relevance
“…In the technology fields, enterprises paid more attention to building quality, operation performance of construction machinery, and maturity of industrialization technology. Furthermore, some research projects focused on information and communication technology in the construction industrialization fields [37,40,64,65]. Experts suggested that the application level of prefabricated components in projects depended on the implementation of construction industrialization technology [37,40,64,65].…”
Section: Challenges In Industrializationmentioning
confidence: 99%
See 1 more Smart Citation
“…In the technology fields, enterprises paid more attention to building quality, operation performance of construction machinery, and maturity of industrialization technology. Furthermore, some research projects focused on information and communication technology in the construction industrialization fields [37,40,64,65]. Experts suggested that the application level of prefabricated components in projects depended on the implementation of construction industrialization technology [37,40,64,65].…”
Section: Challenges In Industrializationmentioning
confidence: 99%
“…The factors included: (1) general awareness [37][38][39][40]; (2) technical field [41][42][43]; (3) human resource [44][45][46]; (4) cost field [3,4]; (5) university-and-institution cooperation [47][48][49]; (6) policy areas [23,50,51]; and (7) industrial management system [52][53][54]. The first group of factors is reflected in some well-recognized, construction industrialization policies in regard to building kinds and company's stance [55][56][57][58].…”
Section: Challenges In Industrializationmentioning
confidence: 99%
“…Table 2 shows a summary of the factors identified in the literature review. Eastman et al 2008;Post 2008;Young et al 2008;Yan, Damian 2008;Hartmann, Fischer 2008;Arayici et al 2009Arayici et al , 2011Sacks, Barak 2010;Singh et al 2011;Gerber et al 2011;Nejat et al 2012;Gledson et al 2012;Giel, Issa 2013;Eadie et al 2013;Porwal, Hewage 2013;Zhang, Gao 2013;Migilinskas et al 2013;Volk et al 2014 19 2 Lack of data interoperability (T5) Bernstein, Pittman 2004;Eastman et al 2008;Post 2008;McAdam 2010;Azhar et al 2011;Kim, Anderson 2012;McAuley et al 2012;Rezgui et al 2013;Porwal, Hewage 2013;Aram et al 2013;Migilinskas et al 2013;Gupta et al 2014;Dong et al 2014;Miettinen, Paavola 2014;Volk et al 2014;Cao et al 2015 No. Factors Reference Sum 3 Changes in workflows and inappropriate business models (M4) Bernstein, Pittman 2004;Howell, Batcheler 2004;Méndez 2006;Gilligan, Kunz 2007;Gu et al 2007;…”
Section: Summary Of Factors Identified In the Literature Reviewmentioning
confidence: 99%
“…Furthermore, a web survey conducted by Autodesk (2008) suggests that BIM increases productivity after an average of three to four months, is more accessible than general CAD applications, enhances workflow after training, benefits owners, designers, and contractors, reduces the risk of design error, and enables communication and coordination among the project team. Although BIM has many benefits, there are also limitations and barriers that have slowed BIM application (Yan, Damian 2008;Zhang, Gao 2013), and BIM application is still in an infant stage to some extent (Cao et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…There are academic studies in a considerable amount of countries: China (Xu, Feng & Li, 2014;Cao et al, 2015;Zhang, Wang, Chen & He, 2014;Ding, Zuo, Wu & Wang, 2015); Denmark (Anker Jensen & Jóhannesson, 2013;Movsisyan, 2016), Iceland (Kjartansdóttir, 2012), India (Luthra, 2010;Kumar & Mukherjee, 2009), Malaysia (Enegbuma & Ali, 2011;Teo, 2012;Latiffi, Mohd, Kasim & Fathi, 2013;Mohd-Nor & Grant, 2014), Portugal (Carvalho, 2016;Silva, Salvado, Couto & Azevedo, 2016), South Africa (Kekana, Aigbavboa & Thwala, 2014;Froise & Shakantu, 2014), Spain (Silvia, del Solar, de la Peña & Vivas 2017), Sweden (Hooper, 2015), United Kingdom (Eadie, Browne, Odeyinka, McKeown & McNiff, 2015;Khosrowshahi & Arayici, 2012), United States (Sattineni & Bradford, 2011), and various cross-country comparisons (Bui, Merschbrock & Munkvold, 2016;Gu, Singh, Tylor, London & Brankovic, 2010;Jung & Lee, 2015;Kassem, Succar & Dawood, 2013;Smith, 2014;Wong et al, 2009;Wong, Wong & Nadeem, 2010).…”
Section: Background State Of the Artmentioning
confidence: 99%